Connected oscillations in a nonlinearly coupled system - Dao, Nguyen Van (Vietnam Journal of Mechanics, 2003)
A single-mass plane system subjected to symmetric restoring forces can strongly oscillate in the direction which is free from the external excitation. The raising oscillation is called the connected one. This phenomenon exists only in nonlinear systems under certain resonance conditions and was first investigated by Kononenko V. 0